Glycinin, b-conglycinin and a-amylase behaviour in artificially deteriorated and not deteriorated soybean - Salinas, Adriana Rita; Yoldjian, Ana Maria; Dietrich, María Lucrecia; Craviotto, Roque Mario; Bisaro, Vilma (Pesquisa Agropecuaria Brasileira, 2002)
The objective of this research was to study the behaviour of the storage proteins glycinin and <span style="font-size: 12pt; font-family: Symbol; mso-ansi-language: EN-US; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';">b-conglycinin and the <span style="font-size: 12pt; font-family: Symbol; mso-ansi-language: EN-US; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';">a-amylase activity in artificially deteriorated and not deteriorated soybean [Glycine max (L.) Merr.] seeds of 10 cultivars. The seeds were submitted to two treatments: deteriorated by accelerated aging and not deteriorated seeds. The presence of glycinin and <span style="font-size: 12pt; font-family: Symbol; mso-ansi-language: EN-US; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';">b-conglycinin were determined in seeds with 0, 3 and 8 days of germination using polyacrylamid gel electrophoresis (SDS-PAGE). The <span style="font-size: 12pt; font-family: Symbol; mso-ansi-language: EN-US; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';">a-amylase activity was biochemically determined in seeds with 0, 3, 8 and 12 days of germination. There were no differences in the presence of glycinin and <span style="font-size: 12pt; font-family: Symbol; mso-ansi-language: EN-US; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';">b-conglycinin electrophoretic bands in not deteriorated seeds until 8 days of germination. The deteriorated seeds showed a similar behaviour to the not deteriorated seeds. The <span style="font-size: 12pt; font-family: Symbol; mso-ansi-language: EN-US; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';">a-amylase activity increased in seeds until the eighth day of germination and decreased to the twelfth day. The enzymatic activity of the deteriorated seeds decreased with respect to that not deteriorated. The artificially deterioration did not affect the presence of glycinin and <span style="font-size: 12pt; font-family: Symbol; mso-ansi-language: EN-US; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';">b-conglycinin but modified the <span style="font-size: 12pt; font-family: Symbol; mso-ansi-language: EN-US; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';">a-amylase activity until the twelfth day of germination. The studied cultivars showed a differential behaviour to the activity of this enzyme.